University language education: Lessons of forced transition to teaching online - E. B. Yastrebova; M. A. Chigasheva; S. V. Evteev (Russian State Vocational Pedagogical University, 2022)
Introduction. The unexpected transition to online teaching in spring 2020 resulted in educational institutions differently equipped in terms of technology, methodology and academic staff preparedness. Moreover, educational institutions faced with a totally new working environment. One may assume that during the pandemic, education systems of most countries crossed the Rubicon, and now there is no going back. What learning and teaching will be like in the future depends, to a large extent, on the lessons the teaching community will learn.The aim of the research was to find out how successful the emergency transition to teaching foreign languages online was and to identify technological resources necessary to maintain the quality of foreign language teaching and learning in different educational formats.Methodology and research methods. The research was carried out in line with the learner- centered activity approach and principles of distant teaching and learning; it also included analysis of online teaching practices across the world before and during the COVID-19 pandemic. The research data was collected via three surveys conducted (with Google forms) among foreign language teachers of MGIMO University (1329 questionnaires) in April, June and September, 2020; 15 heads of foreign language(s) departments (July 2020), and 201 MGIMO students (September 2020). The data was analysed using IBM SPSS Statistics: correlation and cross tabulation analyses, linear regression analysis, and ANOVA.Results. In the course of the research, the correlations between class activities, selfstudy assignments, forms of assessment, and students' engagement in learning have been established; as well as the fact that individual approach in teaching has a positive effect on students' activity, responsibility and academic independence. Furthermore, the problems in online teaching have been identified: classes were not communicative enough, nor teaching sufficiently individualised; besides, the quality of assessment declined with the transition to online learning format.Scientific novelty. An attempt has been made to evaluate the experience of remote teaching foreign languages at university level after the emergency shift to online learning format, and to find out its potential for maintaining (and, in prospect, improving) the quality of language education.Practical significance. Class activities, self-study assignments and forms of testing found the most effective in this research can be of use to foreign language teachers working online. The need to provide individual trajectories for students to develop communicative competence in a foreign language has been established, which is important for course, programme and teaching materials designers.